What Is Domestic Violence? - Kathleen Beall; Heidi Radunovich (EDIS)
Domestic violence can come in many forms and can happen to anyone. It is found all across the world and has a long-standing history in nearly every society. Domestic violence can present itself in many different ways, including sexual violence, physical violence, and emotional violence. In this 3-page fact sheet, we break down each of these types of abuse further to better understand what they really mean. Written by Kathleen Beall and Heidi Radunovich, and published by the UF Department of Family, Youth and Community Sciences, December 2014. (Photo: iStock/Thinkstock.com)